Live imaging screen reveals that TYRO3 and GAK ensure accurate spindle positioning in human cells - Wolf Benita; Busso Coralie; Gönczy Pierre (University of Dundee, 2019)
Proper spindle positioning is crucial for spatial cell division control. Spindle positioning in human cells relies on a ternary complex comprising Gαi1-3, LGN and NuMA, which anchors dynein at the cell cortex, thus enabling pulling forces to be exerted on astral microtubules. We developed a live imaging siRNA-based screen using stereotyped fibronectin micropatterns to uncover components modulating spindle positioning in human cells, testing 1280 genes, including all kinases and phosphatases. We thus discover 16 components whose inactivation dramatically perturbs spindle positioning, including Tyrosine receptor kinase 3 (TYRO3) and cyclin G associated kinase (GAK). TYRO3 depletion results in excess NuMA and dynein at the cell cortex during metaphase, as upon blocking Phosphatidylinositol 3-kinase (PI3K), which TYRO3 activates. Furthermore, depletion of GAK leads to impaired astral microtubules, as upon down-regulation of Clathrin, with which GAK interacts. Overall, our work uncovers novel components and mechanisms governing spindle positioning in human cells.
Keywords: Life Sciences; Mitosis; Spindle